The worship architect: a blueprint for designing culturally relevant and biblically faithful services - Cherry, Constance M. (Baker Academic, a division of Baker Publishing Group, 2021)
"Shows how to create services that are faithful to Scripture, historically conscious, relevant to God, Christ-centered, and engaging for worshipers of all ages"--